Samuel Hartlib his legacie: or An enlargement of the Discourse of husbandry used in Brabant and Flaunders; wherein are bequeathed to the Common-wealth of England more outlandish and domestick experiments and secrets in reference to universall husbandry. Entered according to the late Act concerning printing. [electronic resource] : (1651)
Summary goes here